Flexible Quasi‐Solid‐State Sodium‐Ion Capacitors Developed Using 2D Metal–Organic‐Framework Array as Reactor. Issue 13 (23rd January 2018) - Xu, Dongming; Chao, Dongliang; Wang, Huanwen; Gong, Yansheng; Wang, Rui; He, Beibei; Hu, Xianluo; Fan, Hong Jin
Abstract: Achieving high‐performance Na‐ion capacitors (NICs) has the particular challenge of matching both capacity and kinetics between the anode and cathode. Here a high‐power NIC full device constructed from 2D metal–organic framework (MOFs) array is reported as the reactive template. The MOF array is converted to N‐doped mesoporous carbon nanosheets (mp‐CNSs), which are then uniformly encapsulated with VO2 and Na3 V2 (PO4 )3 (NVP) nanoparticles as the electroactive materials. By this method, the high‐power performance of the battery materials is enabled to be enhanced significantly. It is discovered that such hybrid NVP@mp‐CNSs array can render ultrahigh rate capability (up to 200 C, equivalent to discharge within 18 s) and superior cycle performance, which outperforms all NVP‐based Na‐ion battery cathodes reported so far. A quasi‐solid‐state flexible NIC based on the NVP@mp‐CNSs cathode and the VO2 @mp‐CNSs anode is further assembled. This hybrid NIC device delivers both high energy density and power density as well as a good cycle stability (78% retention after 2000 cycles at 1 A g −1 ). The results demonstrate the powerfulness of MOF arrays as the reactor for fabricating electrode materials. Abstract : Metal–organic framework (MOF)‐derived electrodes for a Na‐ion capacitor . Mesoporous carbon nanosheet arrays are fabricated from 2D Co/Zn‐MOF array, on which anode material VO2 and cathode Na3 V2 (PO4 )3 thin films are deposited. The assembled solid‐state flexible Na‐ion capacitor shows high‐rate performance.